Korupsi Menurut Ariyo Aṭṭhaṅgiko Maggo di dalam Ajaran Buddha Gotama - Linawati Linawati; Alexander Candra (Dhammavicaya : Jurnal Pengkajian Dhamma, 2021)
Purpose - This study examines the problems of corruption in Buddhism to get a solution in an effort to prevent the increaseof corruption in the community according to the view of Buddhism based on the Tripitaka scriptures so that Indonesianpeople can live safely, peacefully and prosperously.Design/methodology/approach This research is a descriptive-qualitative method of normative approach using secondary datasourced from interviews with Buddhist leaders, print media, electronic media, the internet and literature books such as theBuddhist scriptures namely the Tripitaka (Sutta, Vinaya and Abhidhamma Pitaka) and the Eradication Law Corruption thenanalyzes and draws conclusionsResearch Limitation/Implication - Based on the study of theories from the literature book and the opinions of resourcepersons related to corruption in the view of Buddhism.